Long Non-Coding RNA and mRNA Expression Analysis in Liver of Mice With Clonorchis sinensis Infection - Han, Su; Zhang, Xue-Li; Jiang, Xu; Li, Xiang; Ding, Jian; Zuo, Li-Jiao; Duan, Shan-Shan; Chen, Rui; Sun, Bei-Bei; Hu, Xin-Yi; Gao, Yan-Nan; Zhang, Xiao-Li (Frontiers in Cellular and Infection Microbiology, 2022)
Clonorchiasis is recognized as an important zoonotic parasitic disease worldwide. However, the roles of host long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs) in the response to Clonorchis sinensis (C. sinensis) infection remain unknown. Here we compared the expression of lncRNAs and mRNAs in the liver tissue of mice infected with C. sinensis, in order to further understand the molecular mechanisms of clonorchiasis. A total of 388 lncRNAs and 1,172 mRNAs were found to be differentially expressed with absolute value of fold change (FC) ≥ 2.0 and P < 0.05 by microarray. Compared with controls, Gm6135 and 4930581F22Rik were the most over- and under-expressed lncRNAs; flavin containing monooxygenase 3 (Fmo3) and deleted in malignant brain tumors 1 (Dmbt1) were the most over- and under-expressed mRNAs. Moreover, functional annotation showed that the significantly different mRNA were related with “FOXO signaling pathway”, “Wnt signaling pathway” and “AMPK signaling pathway”. Remarkably, lncRNA Gm8801 were significantly correlated with mRNA glycerol-3-phosphate acyltransferase mitochondrial (Gpam), insulin receptor substrate 2 (Irs2) and tumor necrosis factor receptor superfamily member 19 (Tnfrsf19) in co-expression networks. These results showed that the expression profiles of lncRNAs and mRNAs in liver changed after C. sinensis infection. Our results provided valuable insights into the lncRNAs and mRNAs involved in clonorchiasis pathogenesis, which may be useful for future control strategies.